Deleterious Effects of Molting on the Morpho-physiology of Japanese Quail Layers (Coturnix japonica) - Arora, Kashmiri L.; Vatsalya, Vatsalya (International Journal of Poultry Science, 2011)
Molting is a natural physiological phenomenon involving the periodic replacement of old feathers with new ones in the avian species. During mid-November an extensive loss of feathers in Japanese quail was observed in our breeding colony. The cause of molting could not be established, however, lower ambient temperatures may have played a major role and the decrease in day length could not be ruled out as a contributing factor. This study was conducted to correlate some aspects of the molting process using various physiological and morphometric parameters. Forty healthy 125-days old layers, hatch-mates, of approximately similar body weights (130.0±3.9 g) and in peak production were used for cohort evaluation of the molting process. Most of the birds lost feathers extensively from the cervical, thorax and dorsum areas, while some did not molt and continued laying eggs as usual, serving as a premolting control group. The molting birds drastically lost body weight weighing on average 117.5 g compared to 130.0 g in the control group and ceased egg production completely. There was a significant increase in blood glucose (293.03 mg/dL vs. 222.11 mg/dL), an increase in PCV values (47.14% vs. 41.43%) and a decrease in total plasma proteins (3.5 g/dl vs. 5.56 g/dl) and oviducts (1.55 g vs. 5.78 g, a decrease of 73.2%). Ovarian follicles underwent atresia and resorption. Birds that recovered from the molt resumed egg production and regained their body weights showing similar morpho-physiological measures of the control values, which changed during the molting phase. Scientists working with Japanese quail should be fully aware of the physiology of the molting process and its impact on on-going studies involving growth, physiology, endocrinology, nutrition, reproduction and toxicology.